2003
DOI: 10.1002/mame.200390035
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Modification of Polystyrene‐block‐polybutadiene‐block‐polystyrene/Magnesium Hydroxide Composites, 1

Abstract: Composites based on polystyrene‐block‐polybutadiene‐block‐polystyrene (SBS triblock thermoplastic elastomer) and magnesium hydroxide (Mg(OH)2) (5–60 wt.‐%) have been prepared by twin screw extrusion. Interfacial modifiers included dispersants, i.e., isostearic acid, oleic acid, stearic acid; and coupling agents, i.e., maleanised polybutadiene and vinyltriethoxysilane. In each case, approximately one monolayer of treatment was used. A dual bore motor driven extrusion rheometer was used for assessment shear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The flow properties of the PPBC2/GCC composite melts were compared at 200 • C using a Rosand RH-7 dual bore capillary rheometer; the method is described in an earlier publication. Elongational viscosity, as well as the normal shear flow parameters, were determined [17].…”
Section: Mechanical and Rheological Responsesmentioning
confidence: 99%
“…The flow properties of the PPBC2/GCC composite melts were compared at 200 • C using a Rosand RH-7 dual bore capillary rheometer; the method is described in an earlier publication. Elongational viscosity, as well as the normal shear flow parameters, were determined [17].…”
Section: Mechanical and Rheological Responsesmentioning
confidence: 99%
“…To improve the compatibility between inorganic fillers and polymer materials, surface modifiers have been applied including macromolecular surface modifiers16–18 and small‐molecular‐weight ones, such as surface active agents, silane coupling agents, and titanate coupling agents 13, 19–28. Compared with macromolecular surface modifiers, small‐molecular‐weight ones had characteristics of low‐price and facile processing, so they have been applied more popularly.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the compatibility between inorganic fillers and polymer materials, surface modifiers have been applied including macromolecular surface modifiers [16][17][18] and small-molecular-weight ones, such as surface active agents, silane coupling agents, and titanate coupling agents. 13,[19][20][21][22][23][24][25][26][27][28] Compared with macromolecular surface modifiers, small-molecularweight ones had characteristics of low-price and facile processing, so they have been applied more popularly. As for the polyolefin (PO)/MH systems, researchers have tried many different kinds of smallmolecular-weight surface modifiers to the composites including stearate, 19,20 oleate, 21,22 and silane coupling agents, 13,[23][24][25][26][27] and found that silane coupling agents were quite efficient to improve the compatibility of polyolefin/MH composites for the active hydroxyl groups of MH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So compatibilizers are also termed “polymer coupling agents.”11, 12 Many studies about polyolefin/ATH composites were focused on the effects of coupling agents or compatibilizers. Liauw et al systematically studied the effects of various coupling agents on the mechanical properties of polymer/MH composites 5, 13–30. A recent work reported by Hippi et al showed that the presence of compatibilizers could improve both stiffness and toughness of PE/ATH composites while FR properties of the composites remained unchanged 3.…”
Section: Introductionmentioning
confidence: 99%